Mitochondrial DNA Analysis by Denaturing High-Performance Liquid Chromatography for the Characterization and Separation of Mixtures in Forensic Samples - Kristinsson, Richard (2011)
A mixture of different mtDNA molecules in a single sample is a significant obstacle to the successful use of standard methods of mtDNA analysis (i.e., dideoxy dye-terminator sequencing). Forensic analysts often encounter either naturally occurring mixtures (e.g., heteroplasmy) or situational mixtures typically arising from a combination of body fluids from separate individuals. The ability to accurately resolve and interpret these types of samples in a timely and cost efficient manner would substantially increase the power of mtDNA analysis and potentially provide valuable investigative information by allowing its use in cases where the current approach is limited or fails. Therefore, this research was aimed at developing a strategy for the use of Denaturing High-Performance Liquid Chromatography (DHPLC) as a developmentally-validated forensic application for resolving mixtures of mtDNA. To facilitate the adoption of this technology by the forensic community, a significant effort has been made to ensure that this technology meets the Scientific Working Group on DNA Analysis Methods (SWGDAM) developmental validation criteria and interfaces smoothly with previously validated methods of forensic mtDNA analysis. To do this, the method developed using DHPLC employs mtDNA amplicons, PCR conditions and DNA sequencing protocols validated for use in forensic laboratories. These factors are essential in implementing DHPLC analysis in a forensic casework environment and for the admissibility of DHPLC and Linkage Phase Analysis in court